Ultrasound measurement of optic nerve sheath diameter in patients with a clinical suspicion of raised intracranial pressure. Issue 8 (15th August 2010) - Major, Robert; Girling, Simon; Boyle, Adrian
Abstract : Background: To assess if ultrasound measurement of the optic nerve sheath diameter (ONSD) can accurately predict the presence of raised intracranial pressure (ICP) and acute pathology in patients in the emergency department. Methods: This 3-month prospective observational study used ultrasound to measure the ONSD in adult patients who required CT from the emergency department. The mean ONSD from both eyes was measured using a 7.5 MHz ultrasound probe on closed eyelids. A mean ONSD value of >0.5 cm was taken as positive. Two radiologists independently assessed CT scans from patients in the study population for signs of raised ICP and signs of acute pathology (cerebrovascular accident, subarachnoid, subdural or extradural haemorrhage and tumour). Specificity, sensitivity and κ values, for interobserver variability between reporting radiologists, were generated for the study data. Results: In all, 26 patients were enrolled into the study. The ONSD measurement was 100% specific (95% CI 79% to 100%) and 86% sensitive (95% CI 42% to 99%) for raised ICP. For any acute intracranial abnormality the value of ONSD was 100% specific (95% CI 76% to 100%) and 60% sensitive (95% CI 27% to 86%). κ Values were 0.91 (95% CIs 0.73 to 1) for identification of raised ICP on CT and 0.84 (95% CIs 0.62 to 1) for any acute pathology on CT, between the radiologists. Conclusions: This study shows that ultrasound measurement of ONSD is sensitive and specific for raised ICP in the emergency department. Further observational studies are needed but this emerging technique could be used to focus treatment in unstable patients.